Modelo de satisfação de estudantes na Educação Profissional : integrando qualidade em serviços, resultados da aprendizagem, empregabilidade, imagem, valor e lealdade - Silva, Jorge Henrique de Oliveira (Universidade Federal de São Carlos, 2017)
Student satisfaction is a response from the student evaluation regarding several aspects of the educational experience. The objective of this study is to investigate the effects of service quality, learning outcomes, employability, value and institutional image on the satisfaction of students enrolled in Vocational Education, considering the multiple relationships between the mentioned factors and the impacts on the student loyalty. A conceptual model was proposed that differs from others because it adds two important constructs for the educational context - learning outcomes and employability. Both are especially relevant in Vocational Education. For the validation of the model, a quantitative survey was carried out with students enrolled in courses offered by the Federal Institute of Education, Science and Technology of São Paulo. A valid sample of 505 students was obtained. The data were analyzed using Structural Equation Modeling The results showed that the final model has a large capacity to explain the variation in factors related to student satisfaction. It was identified that educational quality of services and employability have the greatest effects on student satisfaction. While the value that the student attributes to the educational experience is mainly determined by learning outcomes. Theoretical and managerial implications are made.
Student satisfaction model in Vocational Education : integrating service quality, learning outcomes, employability, image, value and loyalty
Keywords: Qualidade em serviços; Satisfação de clientes; Educação Profissional; Satisfação de estudantes; Resultados da aprendizagem; Empregabilidade; Imagem; Valor; Lealdade; Service quality; Customer satisfaction; Learning outcomes; Employability; Image; Value; Loyalty; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO